Reservoir operation planning and cropping pattern optimization for Chamravattom regulator - cum bridge - GULJA S. NAIR; Neenu Peter; Prajitha M; Er. Rema K. P (Guide) (Tavanur 2008 Kelappaji College of Agricultural Engineering and Technology)
Reservoir operation planning and cropping pattern optimization for Chamravattom regulator - cum bridge
Reservoir operation planning and cropping pattern optimization for Chamravattom regulator - cum bridge